Manipulating the abundance of Lepthyphantes tenuis (Araneae : Linyphiidae) by field margin management - Bell, JR; Johnson, P; Hambler, C; Haughton, A; Smith, H; Feber, R; Tattersall, F; Hart, B; Manley, W; Macdonald, D (2002)
Populations of the linyphiid spider Lepthyphantes tenuis were sampled in field margins in May, July and September in 1990-1991 and 1995-1996. Field margins were subjected to 10 grassland management regimes, which included the effects of spraying the herbicide glyphosate, cutting, leaving vegetation in situ after the cut, sowing and a control. These treatments were randomised within six complete blocks at the University of Oxford's farm at Wytham. Cutting vegetation had an immediate effect on number of L. tenuis in both spring and summer. Cutting margins in summer had a more persistent effect on populations of L. tenuis than did cutting margins in spring. The effect of cutting was not mitigated by leaving cut vegetation in situ, but no cutting ensured higher number of L. tenuis in margins, an indication that height and structural complexity of grassland vegetation were important in determining population size. Significantly fewer spiders were found in July and September plots which had been sprayed with herbicide in late June/early July. However, spider numbers were not affected by glyphosate application when samples were taken nearly a year later. Sowing a wildflower seed mixture had no significant effects on number of this generalist predator although other invertebrate groups did benefit. Field margins provided an excellent source habitat for L. tenuis. Habitats that border crop fields acted as a refugia for many other beneficial invertebrates and should be retained as an important component of the agricultural landscape. © 2002 Elsevier Science B.V. All rights reserved.